ANALISIS DETERMINAN KEMISKINAN SEBELUM DAN SESUDAH DESENTRALISASI FISKAL - -, USMAN; M. SINAGA, BONAR; SIREGAR, HERMANTO (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006, 2012)
Understanding about determinant factors of poverty will help policy maker to ensure that the poor get benefit from the economic policy. In general, this study aim to analyze the changes of determinant factors of poverty before and after the implementation of fiscal decentralization. Using the model, this study found that in community factor there are some variables have change from 1999 to 2002. One of these variables is road infrastructure. In 2002 (after fiscal decentralization period), the quality of road was worse than before so the impact is the poverty was increase. This study shows that if both central and local government concern with poverty reduction then they have to notice some sectors such as agriculture, education, family health, and infrastructure. These variables are the determinant factors of poverty.
Keywords: Determinant, Poverty, Decentalization, Fiscal